Hurst's the heart manual of cardiology - O'Rourke, Robert A.; Walsh, Richard A.; Fuster, Valentin (McGraw-Hill Medical, 2009)
A complete pocket guide to diagnosing and treating the full range of heart problems. Summarizing the clinical sections of Hurst's the Heart, 12e, this point-of-care resource covers the key points of cardiovascular pathophysiology, diagnosis, and treatment in a quick-access presentation, making it essential for rounds, at the bedside, or on the wards.